The presidential pardon of Fujimori: political struggles in Peru and the subsidiary role of the Inter-American Court of Human Rights - Cornejo Chavez, Leiry (International journal of transitional justice, 2019)
In 2017, former Peruvian president Alberto Fujimori was pardoned after serving less than half of a 25-year sentence for human rights violations. The measure was taken amidst political turmoil and an impeachment process led by the Fujimorista party against former president Pedro Pablo Kuczynski. Fujimori’s victims in the Barrios Altos and La Cantuta cases requested the Inter-American Court of Human Rights (IACtHR) to annul the pardon due to its incompatibility with Peru’s human rights obligations. The IACtHR decided that it was for the Peruvian courts to exercise jurisdictional control over the pardon, thus affirming its subsidiary role. Through an examination of the political situation, the underlying principles of the IACtHR’s jurisprudence on amnesties, and rule of law and international standards, this article argues that the IACtHR had sufficient grounds to overturn the pardon. The court’s resolution to refer the matter to the Peruvian jurisdiction may be explained by an increasing awareness of its subsidiary role, particularly regarding sensitive political issues.